Assessing environmental concerns, knowledge and health consciousness in young adults’ organic food choices - Nusrah Samat; Sakti Sethumadavan; Amily Fikry; Siti Fatimah Md Shariff; Noor Fzlinda Fabeil (AMH International, 2025)
The trend towards buying organic food is declining among young adults, which raises concerns about factors influencing their purchasing behavior. This study investigates factors affecting young adults’ buying behavior of organic food products, including environmental concerns, knowledge, and health consciousness. Survey data was collected from 100 young adults in Selangor, Malaysia. Multiple regression analysis was conducted to analyze the data. The results showed that knowledge about organic food was the strongest predictor of young adults’ organic food purchasing behavior. In addition, concern for the environment had a significant positive influence on young adults’ organic food purchasing behavior, while health consciousness showed no significant influence. These findings offer practical implications for manufacturers: to provide clear product details that can enhance consumers’ knowledge and highlight environmental advantages in marketing strategies to encourage consumption. This study contributes to the literature by highlighting the value of environmental awareness and knowledge of organic food and shedding light on the minor influence of health awareness-a topic that has received less attention in other studies.